Gender-Differentiated Education in Colombia (19th Century): Discourses and Policies: Discursos y políticas (TEL Tempo, Espaço e Linguagem, 2026)
This article examines how nineteenth-century Colombian educational policies produced a sex-differentiated model of education. It analyzes four mechanisms: administrative provisions, teacher regulation, admission criteria, and content distribution. It demonstrates how the school system functioned as a technology of government that contributed to the reproduction of the gender order in the nation-state building project (1820-1900).